Implementation of Differentiated Content Learning Based on Students' Learning Readiness in the Material of Presenting Data in the Form of Scatter Diagrams - Kharisma, Bella; Napitupulu, Bettisari; Tandililing, Pitriana; Lumbantobing, Happy; Sirampun, Elsi (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The Implementation of Content Differentiated Learning Based on Students' Readiness in the Topic of Presenting Data in the Form of a Scatter Plot in Class XI-7 of SMA Negeri 1 Jayapura. This research is a descriptive qualitative study aimed at describing the implementation of content differentiated learning based on students’ readiness in the topic of presenting data in the form of a scatter plot. The subjects of this study were 37 students from Class XI-7 of SMA Negeri 1 Jayapura, selected through purposive sampling technique.. The research instruments used included a teaching module, diagnostic assessment, individual test, and teacher observation sheet. The results of the diagnostic assessment were used to categorize students into three levels of readiness: low, medium, and high. Students were grouped into seven groups: three low-readiness groups, three medium-readiness groups, and one high-readiness group. The differentiated learning was implemented effectively, as indicated by the teacher’s observation score of 86.875% and the peer observer’s score of 88.125%, both of which fall under the “very good” category. The results of the individual test showed that 27 out of 37 students (72,97%) met the KKM, while 12 students (27,03%) did not. Among the medium- readiness group, 5 students did not meet the criteria, and among the low-readiness group, 5 students were not yet successful. These findings indicate that content-differentiated learning positively impacts students' learning outcomes, although further support is needed for those in the low-readiness group.